Analisis Sistem Website Beras Kita Sejahtera Dalam Menunjang Kelancaran Logistik Pangan - Dewi Cahya Pertiwi; Adam Ferdiansyah; Wahyu Hujatul Ilmi (Universitas 17 Agustus 1945 Semarang, 2023)
As science and technology develop, many things change with the times, everything without the distance of time and space can be accessed anywhere and anytime. Not only with social media in the development of food and logistics technology to reach the stage of a new era that is simpler quickly and precisely by utilizing digitalization to make it easier for someone to transact and create suppy logistics that is useful and on target, namely by using the website method, With this website, safe purchase transactions are fast and appropriate to create a stable food supply. We know that Indonesia still relies on importing rice from outside countries for the food needs of its people, without us knowing that the improvement of the digital system can be able to encouraging food suppliers in Indonesia, with the existence of this website, it is expected to be a bright hope in logistics supply in Indonesia.